Performance of Subcarrier Intensity Modulation over an Imprecise Gamma-Gamma Channel - Ibrahim, Abdulgani; Erdogan, Eylem; Gucluoglu, Tansal (IEEE, 2018)
Free-space optical (FSO) Communication is a technology that promises several advantages over the conventional radio-frequency (RF) wireless communication, including high data rates and lack of licensing. However, the performance of an FSO communication system can be deteriorated by the atmospheric turbulence. In this paper, we are investigating the average bit error rate of a subcarrier intensity modulation based on phase shift keying (PSK) over an imprecise Gamma-Gamma fading FSO link.
Keywords: Free-space optical; Gamma-Gamma turbulence; Imprecise channel; Subcarrier intensity modulation; Bit error rate; OPTICAL WIRELESS COMMUNICATIONS; ATMOSPHERIC-TURBULENCE; COMMUNICATION-SYSTEMS; LINKS; PROBABILITY; MODEL; Engineering; Telecommunications